Islamic Sermon at Islamic Boarding Schools in Developing Public Speaking Skills - Arifin, Faisal; Yaya, Yaya; Hafidz, Zaini (STAI AL-FALAH CICALENGKA, 2022)
This research departs from extracurricular activities which are one of the activities in schools and non-formal educational institutions, which are oriented towards developing self-capacity, channeling the capacity of students' interests and talents. This extracurricular is an additional lesson outside of class hours, the purpose of this extracurricular activity is to increase the interests and talents of students. The purpose of this study was to find out how the concept of missionary activities, the implementation of missionary activities, and to find out what were the inhibiting and supporting factors of missionary activities at the Nurul Falah Bungbulang Islamic Boarding School. This study uses a qualitative approach with a descriptive method. To obtain the information and data needed in the study, the researchers used data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results showed that the extracurricular activities of muballighin at the Nurul Falah Bungbulang Islamic boarding school had been going well, this activity was carried out on the basis of need with the intention that students had skills, courage, honesty and discipline, then this activity aimed to make students mentally strong and have the ability to speak in public. This extracurricular activity of the preacher is carried out every Sunday night alternately with other activities, all students who have registered as participants should attend and take part in these activities. The students who are selected as champions will be trained and fostered better, so that they can be used as participants in other activities outside the pesantren. The expertise gained from this missionary activity is that students have the ability to speak in public, students have the ability to communicate, and students have the ability to read situations and conditions around them. The inhibiting factors for these activities are the psychological factors of students such as fear, shame, and hesitation to appear in public, then ineffective time management, and the unpreparedness of students. While the supporting factors for these activities include the cohesiveness of the management, supporting facilities and infrastructure, and enthusiastic students. Thus, it can be ascertained that the extracurricular activities of the muballighin at the Nurul Falah Bungbulang Islamic boarding school have been going well. Keywords: Da'wah, Extracurricular, Muballighin, Islamic Boarding School. Abstrak Penelitian ini bertolak dari kegiatan ekstrakurikuler yang merupakan salah satu kegiatan di sekolah maupun di lembaga pendidikan non-formal, yang berorientasi untuk pengembangan kapasitas diri, penyaluran kapasitas minat dan bakat santri. Ekstrakurikuler ini merupakan pelajaran tambahan di luar jam pelajaran, tujuan kegiatan ekstrakurikuler ini adalah untuk meningkatkan minat dan bakat peserta didik. Tujuan penelitian ini adalah untuk mengetahui bagaimana konsep kegiatan muballighin, implementasi kegiatan muballighin, serta untuk mengetahui apa saja faktor penghambat dan faktor pendukung kegiatan muballighin di pesantren Nurul Falah bungbulang. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Untuk memperoleh informasi dan data-data yang diperlukan dalam penelitian, maka peneliti menggunakan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Teknik analisis data yang digunakan adalah reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukan bahwa kegiatan ektrakurikuler muballighin di pesantren Nurul Falah Bungbulang telah berjalan dengan baik, kegiatan ini dilaksanakan atas dasar kebutuhan dengan maksud agar santri memiliki keterampilan, keberanian, kejujuran dan kedisiplinan, kemudian kegiatan ini bertujuan agar santri memiliki mental yang kuat dan memiliki kemampuan berbicara didepan umum. Kegiatan ektrakurikuler muballighin ini dilaksanakan setiap malam minggu secara bergantian dengan kegiatan lain, seluruh santri yang telah terdaftar menjadi peserta hendaknya hadir dan mengikuti kegiatan tersebut. Santri yang terpilih menjadi juara akan dilatih dan dibina lebih baik, sehingga mereka bisa dijadikan peserta pada kegiatan lain diluar pesantren. Keahlian yang didapat dari kegiatan muballighin ini adalah santri memiliki kemampuan berbicara didepan umum, santri memiliki kemampuan berkomunikasi, serta santri memiliki kemampuan membaca situasi dan kondisi di sekitar. Faktor penghambat kegiatan tersebut adalah faktor psikologis santri seperti takut, malu, dan ragu untuk tampil didepan umum, kemudian manajemen waktu yang tidak efektif, dan ketidaksiapan santri. Sedangkan faktor pendukung kegiatan tersebut antara lain yaitu kekompakan pengurus, sarana dan prasarana yang mendukung, dan santri yang antusias. Dengan demikian dapat dipastikan bahwa kegiatan ekstrakurikuler muballighin di pesantren Nurul Falah Bungbulang telah berjalan dengan baik. Kata kunci: Dakwah, Ekstrakurikuler, Muballighin, Pesantren.